Blynk App-Based Plant Monitoring System Design - Tanashia Lavenia; Fahmy Rinanda Saputri (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Plantations represent a vital economic sector in Indonesia. However, farmers who rely on plantations for their livelihood often encounter challenges related to air and soil quality, which can significantly impact plant growth. Each type of plant requires specific air and soil conditions to thrive optimally, including factors such as air temperature, humidity, soil moisture, and pH levels. To address these issues, a solution has been developed in the form of a plantation monitoring system that can be accessed remotely and in real-time through cellular and desktop applications. This monitoring system utilizes various sensors, including DHT11 sensors, resistive soil moisture sensors, and soil pH sensors, all of which are meticulously calibrated with digital soil sensors. The collected data can be conveniently monitored and managed through an Internet of Things platform, such as Blynk.Based on the case study, the measurement system that is displayed on Blynk has a range of 0-100 °C for air temperature, 0-100% for air humidity, 0-1000 for soil moisture, and 0-14 for soil pH.